2006
DOI: 10.1007/s11434-006-2196-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms of megadunes and lakes in the Badain Jaran Desert, Inner Mongolia

Abstract: Field observations demonstrate that calc-sinters occurred in the lakes of Badain Jaran Desert. 87 Sr/ 86 Sr ratios, 14 C, δ 13 C and mineral compositions of calc-sinters, and 3 He/ 4 He, 4 He/ 20 Ne, δ 18 O, δ D, pH and TDS of water from springs and lakes are analyzed in detail. The results indicate that the lake water is supplied through deep fault zone. The "kernel" of stabilized dunes in the Badain Jaran Desert perhaps consists of calc-sinters and calcareous cementation layers. Deep-seated groundwater effus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 4 publications
(10 reference statements)
2
36
3
Order By: Relevance
“…Recent work (Wang and Chen, 2018) found considerable overestimation of the groundwater age by the 14 C dating method due to neglect of dead carbon brought on by deep CO 2 emission. In contrast to the fossil groundwater hypothesis, the detectable tritium activities as shown by Wu et al (2017) and many others (Chen et al, 2006;Gates et al, 2008;Yang and Williams, 2003) indicate a modern precipitation source of the BJD groundwater. This suggests that the Qilian Mountains-sourced groundwater flows through hundreds of kilometers over only tens of years.…”
Section: Reanalysis On the Origin Of Groundwater In The Bjdcontrasting
confidence: 59%
See 2 more Smart Citations
“…Recent work (Wang and Chen, 2018) found considerable overestimation of the groundwater age by the 14 C dating method due to neglect of dead carbon brought on by deep CO 2 emission. In contrast to the fossil groundwater hypothesis, the detectable tritium activities as shown by Wu et al (2017) and many others (Chen et al, 2006;Gates et al, 2008;Yang and Williams, 2003) indicate a modern precipitation source of the BJD groundwater. This suggests that the Qilian Mountains-sourced groundwater flows through hundreds of kilometers over only tens of years.…”
Section: Reanalysis On the Origin Of Groundwater In The Bjdcontrasting
confidence: 59%
“…This suggests that the Qilian Mountains-sourced groundwater flows through hundreds of kilometers over only tens of years. We suggest that, due to geological activities, various southwest-northeast deep fault systems exist between the Qilian Mountains and the desert (Chen et al, 2006). Based on the geological conditions and geochemical evidence (helium results), these large deep fault systems are hypothesized to act as a quick passage for the groundwater (Chen et al, 2006(Chen et al, , 2004(Chen et al, , 2012, which explains the detectable tritium in the groundwater.…”
Section: Reanalysis On the Origin Of Groundwater In The Bjdmentioning
confidence: 88%
See 1 more Smart Citation
“…The mean annual wind speed ranges from 2.8 m/s to 4.6 m/s, increasing from the south to the north, with the strongest winds in April and May. The mean annual air temperature ranges from 9.5℃ to 10.3℃, increasing from the south to the north as the elevation decreases (Dong et al, 2004;2009), and the highest air temperature can reach 41℃, while the surface temperature is over 70℃ (Zhu et al, 1980;1992;Chen et al, 2006;Zhao et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…As for water will become, oil and an important controlling component in restricting the development of the global economy and society of the 21 st century [4,5] .Although climate warming has caused to increasing amounts of meltwater on the Tibetan Plateau, but much of this water can't used, reducing the water available for downstream areas and limiting the water consumption of these areas [1,[6][7][8] .There is a lack of understanding and knowing concerning the water quality of these water resource except its importance, Barnett and Huang found that the resultant changes in hydrological conditions on the quality and availability of the water from the Plateau. In recent years, a great many survives have been demonstrated runoff [9] , precipitation, etc, on the water cycle components of the plateau [3] , alpine lake water environment changes on the Tibetan Plateau [10] . But for surface water, only Zheng carried out the Tibetan surface water in 1956 which studies mainly focused on major ions in saline lakes on the Tibetan Plateau is the most comprehensive study [11] and surface water quality of Yangtze Estuary [12] .…”
Section: Introductionmentioning
confidence: 99%